Evaluation Of Treatment Outcome, Health-Related Quality Of Life And Cost Of Treatment In Smear Positive Pulmonary Tuberculosis Patients - Atif, Muhammad (2014)
Despite the effective therapy, tuberculosis (TB) remains one of the major causes of adult morbidity and mortality. Available data show that the burden of TB is slowly increasing in Malaysia. Therefore, this study was conducted with an objective to evaluate the management of new smear positive pulmonary TB (PTB) patients. This management included clinical, health-related quality of life (HRQoL) and economic standpoints at the chest clinic of Hospital Pulau Pinang (HPP), Malaysia. In the first part of this prospective follow-up study, all new smear positive PTB patients who were registered at the chest clinic of HPP, between March 2010 and February 2011, were evaluated for the outcome of their TB treatment. In the second part, new smear positive PTB patients and their family caregivers were invited to self-complete the Short-Form 36 version 2 (SF-36v2) HRQoL questionnaire, while the third part is an incidence-based economic study. The total cost of TB treatment was estimated from the perspective of both provider and patient using appropriate methods.